2016
DOI: 10.3390/nu8080506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beetroot Juice on Recovery of Muscle Function and Performance between Bouts of Repeated Sprint Exercise

Abstract: This study examined the effects of beetroot juice (BTJ) on recovery between two repeated-sprint tests. In an independent groups design, 20 male, team-sports players were randomized to receive either BTJ or a placebo (PLA) (2 × 250 mL) for 3 days after an initial repeated sprint test (20 × 30 m; RST1) and after a second repeated sprint test (RST2), performed 72 h later. Maximal isometric voluntary contractions (MIVC), countermovement jumps (CMJ), reactive strength index (RI), pressure-pain threshold (PPT), crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(134 citation statements)
references
References 66 publications
6
124
1
3
Order By: Relevance
“…The level of CK obtained at the pre-and posttraining time points suggests that a high muscle damage occurs as a result of the RS exercise. This was consistent with the previously published studies in which similar CK values of 592 U/L were registered (Clifford, et al, 2016); however, even much higher values of 776 U/L (Howatson & Milak, 2009) and 1120.7 U/L (Woolley, Jakeman, & Faulkner, 2014) were also reported after different running RS exercises. Interestingly, much lower CK values of 230.6 U/L (Jówko, et al, 2015) and 166 U/L (Bloomer, et al, 2006) were reported in studies investigating cycling RS exercises, which was probably caused by a different muscle action utilized in cycling versus running.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The level of CK obtained at the pre-and posttraining time points suggests that a high muscle damage occurs as a result of the RS exercise. This was consistent with the previously published studies in which similar CK values of 592 U/L were registered (Clifford, et al, 2016); however, even much higher values of 776 U/L (Howatson & Milak, 2009) and 1120.7 U/L (Woolley, Jakeman, & Faulkner, 2014) were also reported after different running RS exercises. Interestingly, much lower CK values of 230.6 U/L (Jówko, et al, 2015) and 166 U/L (Bloomer, et al, 2006) were reported in studies investigating cycling RS exercises, which was probably caused by a different muscle action utilized in cycling versus running.…”
Section: Discussionsupporting
confidence: 93%
“…Namely, peak CK values are usually reached 24 hours after highintensity sport activities in which RS sequences are frequently executed (Silva, et al, 2018). Interestingly, 1-hour post-exercise CK values, reported in some of the above-cited studies, were 362 U/L (Clifford, et al, 2016) and 376 U/L (Woolley, et al, 2014), which was similar to the values obtained in the present study. It can be implicated that the level of muscle damage in our study was even greater, but the measurement time point prevented us from capturing the peak CK values.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, quicker recovery was observed after consumption of BRJ, which resulted in enhanced recovery in counter-movement jumps, reactive strength index and repeated sprint test. This study also found that no mean differences were observed for fastest sprint time or fatigue index after BRJ consumption (Clifford, Bell, et al 2016;Clifford, Berntzen, et al 2016). Some studies have shown a reduction in muscle pain and fatigue associated with exercise induced muscle damage and reduced after with BRJ supplementation Husmann et al 2019).…”
Section: Effects Of Short-term Brj Supplementation In Relation To Trasupporting
confidence: 45%